(untitled) (Revista Apotheke, 2022)
The article discusses the process of investigation and artistic practice that took place from the meetings with groups of women in the sewing and embroidery workshops of a rural community near the city of Lincoln, Argentina, Buenos Aires, during the Second Edition of the International Residency. COMUNITARIA, Arte Contemporáneo y Procesos Sociales, which took place during the month of November 2017. We used embroidery to form a poetic image of our authorial work during this investigation and as a reference for reflections on the construction and deconstruction of expectations created in society and among others. women themselves about art and gender. We imagine a performative force based on the thinking of Gilles Deleuze and Felix Guattari (1995) that mediates the paths and movements that rescue histories of the residency, which we put into perspective from feminist studies and on the relations between art and gender in Latin America. We start from the idea of a nomadic artist, by Cristina Freire (2006) and from the argument developed by Sepúlveda T. and Bustos (2017) that art is a tool for political action when it is guided by a horizontal system of relationships based on attention, encounters, in the stories and in the alternative spaces of listening and concrete actions. Finally, we will show that the expressiveness of embroidery, while serving as a vehicle for a moralizing education system, can be used as a vehicle for communication and a creative space for reflection on the political condition, contesting social and aesthetic hierarchies imposed and pointing to emerging social dynamics in Latin America.